Threatening illness perception and associated factors in early-stage relapsing-remitting multiple sclerosis - Gómez-Ballesteros, Rocío; Sainz de la Maza, Susana; Borges, Mónica; Martín-Martínez, Jesús; Sotoca, Javier; Alonso, Ana; Caminero, Ana B.; Borrega, Laura; Sánchez-Menoyo, José L.; Barrero-Hernández, Francisco J.; Calles, Carmen; Brieva, Luis; et al. (Frontiers in Psychiatry, 2025)
BackgroundMultiple sclerosis is one of the most common causes of neurological disability in young adults, with major consequences for their future lives. Patients with early-stage relapsing-remitting multiple sclerosis (RRMS) experience uncertainty and intense emotions as the diagnosis is disclosed. Illness perception at this point can influence levels of adjustment, coping strategies, treatment adherence, and well-being of the patient. However, there is limited information on patient illness perception surrounding the diagnosis.ObjectiveThe aim of this study was to assess illness perception and associated factors in early-stage RRMS patients.MethodsA multicenter, non-interventional study was conducted. Adult patients with a diagnosis of RRMS, a disease duration of ≤ 3 years, and an Expanded Disability Status Scale (EDSS) score of 0-5.5 were included. The Brief-Illness Perception Questionnaire (B-IPQ) was used to assess the patients’ cognitive and emotional representations of their illness. Different patient-reported measures were used to gather information on pain, fatigue, mood/anxiety, quality of life, symptom severity, feelings of hopelessness, perception of stigma, cognition, hand dexterity, gait, and workplace difficulties. A multivariate logistic regression analysis was performed to assess the association between the patients’ illness perception and demographic and clinical characteristics, as well as patient-reported outcomes.ResultsA total of 189 patients were included (mean age: 36.1 ± 9.4 years, 71.4% females, mean disease duration: 1.4 ± 0.8 years). The median EDSS score was 1.0 (interquartile range: 0.0-2.0). A total of 36.5% of the patients (n=69/189) had a moderate-to-high threatening illness perception, and 45.5% thought that their disease was caused by psychological factors. Higher EDSS scores, symptom severity, poorer psychological quality of life, perception of stigma, and greater hopelessness were predictors of moderate-to-high threatening illness perception.ConclusionsThreatening illness perceptions are common among patients with early-stage RRMS. Identifying these beliefs and their associated factors, and establishing individualized interventions, may help patients deal with their condition.